Investigating the Teaching of English Literature through Narrative Inquiry - Desvalini Anwar (Fakultas Bahasa dan Seni Universitas Negeri Padang, 2012)
This paper seeks to argue for the significant contribution a narrative inquiry can offer for research in education. This work arises from the author’s PhD research that she is currently conducting at Deakin University, Australia. As data analysis is still in progress, this paper should not be regarded as a conclusion of her findings. The author’s intention is to explain how the literary praxis or the teaching of English literature practiced by the academics at the universities in Padang West Sumatra Indonesia can be investigated through narrative inquiry. Narrative inquiry is a study of how humans make meaning of experience by endlessly telling and retelling stories about themselves that both refigure the past and create purpose in the future (Connelly & Clandinin.1998). The focus of scrutiny is on stories told by both the research participants taken from three rounds of individual interviews and the author’s autobiographical narrative. All of these teachers’ stories inform the constraints that operate on them; these teachers teach English literature where English is a foreign language and also where reading is not yet embraced as a daily habit or a joyous task. The autobiography and interviews reflect the choices that the teachers make and thus, show their standpoint. Narrative inquiry significantly offers an opportunity for educators to articulate the realities that they experience in contradiction to the standards prescribed by, for example, the curriculum, as well as develop a reflective practice of their own. It also offers insights of and reflections on teachers’ identity and their professional development. KEYWORDS: Narrative inquiry, autobiographical narrative, stories, reflective practice, interview, literary praxis, constraints, standpoint